2013
DOI: 10.1016/j.jadohealth.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Behavior Among Adolescents: Initiation, Duration, and Exclusivity

Abstract: Purpose Despite a substantial amount of evidence on breastfeeding among non-adolescent mothers, research and strategies uniquely designed to target adolescent mothers are critical as their rates of breastfeeding are disproportionately low and their transition to parenthood is often unlike that of older mothers. Literature to date, however, offers limited evidence for designing effective interventions. Therefore, we aim to fill this gap in the literature by examining breastfeeding behaviors among a cohort of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
71
1
28

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 37 publications
6
71
1
28
Order By: Relevance
“…17,20,21,22,23,24 Adölesan Annelerde Emzirme Oranları Tüm ülkelerde, adölesan annelerin emzirmeye başlama ve emzirmeyi devam ettirme oranı, yetişkin annelere göre daha düşüktür ve birçok adölesan 6 haftadan daha az süre emzirmeyi devam ettirmektedir. 17,25,26,27 Amerika'da (2014) yayınlanan emzirme raporunda, genel emzirme oranı %79,2, ilk 6 ayda sadece anne sütü verme oranı ise %18,8 olarak belirtilmiştir. 28 Center for Disease Control (CDC) 2011 raporuna göre ise, 20 yaş ve altındaki annelerin yalnızca %19,3'ü, 20-29 yaş arasındaki kadınların %36,4'ü, 30 yaş ve üzeri kadınların ise %45'i 3 ay boyunca sadece anne sütü vermektedir.…”
Section: Adölesan Annelerde Emzirmenin Yararlarıunclassified
See 2 more Smart Citations
“…17,20,21,22,23,24 Adölesan Annelerde Emzirme Oranları Tüm ülkelerde, adölesan annelerin emzirmeye başlama ve emzirmeyi devam ettirme oranı, yetişkin annelere göre daha düşüktür ve birçok adölesan 6 haftadan daha az süre emzirmeyi devam ettirmektedir. 17,25,26,27 Amerika'da (2014) yayınlanan emzirme raporunda, genel emzirme oranı %79,2, ilk 6 ayda sadece anne sütü verme oranı ise %18,8 olarak belirtilmiştir. 28 Center for Disease Control (CDC) 2011 raporuna göre ise, 20 yaş ve altındaki annelerin yalnızca %19,3'ü, 20-29 yaş arasındaki kadınların %36,4'ü, 30 yaş ve üzeri kadınların ise %45'i 3 ay boyunca sadece anne sütü vermektedir.…”
Section: Adölesan Annelerde Emzirmenin Yararlarıunclassified
“…Brezilya'da yapılan çalışmalarda, kendi anneleriyle birlikte yaşayan adölesanlarda, sadece anne sütü verme süresinin azaldığı gösterilmiştir. 61 26 tarafından yapılan çalışmada, eşinden şiddet gören adölesan annelerin daha kısa süre emzirdiği belirtilmiştir. 26 Üniversite öğrencileri ile yapılan başka bir çalışmada da, erkeklerin kız öğrencilere göre emzirme konusunda daha az bilgili olduğu ve emzirme konusunda negatif bir tutuma sahip olduğu bulunmuştur.…”
Section: Adölesan Annelerde Emzirmeyi Etkileyen Faktörlerunclassified
See 1 more Smart Citation
“…20 Moreover, data demonstrated that first pregnant mothers were cited as more likely to breastfeed than multiparas. 16,25 In primiparas, intend to breastfeeding was related to prenatal care by obstetrician professional and not cesarean section and in multiparous, was associated with not performing cesarean, the mother have the baby in contact with immediately after birth and residence in rooming for two days or less.…”
Section: 25mentioning
confidence: 99%
“…6 Numerous studies have been conducted to identify factors associated with breastfeeding initiation. [6][7][8][9][10][11][12][13][14][15][16][17] Factors found to be associated with breastfeeding initiation included increasing maternal age, 7 exclusive prenatal care by midwives, 7 continued support from professionals such as lactation consultants and peers, 9,10 sociodemographic factors such as higher levels of education, married or common-law status 17 and higher household incomes. 13 Factors associated with lower rates of breastfeeding initiation were multiple births, preterm birth, not attending antenatal classes, 6 having a high body mass index (BMI) 9,10 and being an adolescent parent.…”
mentioning
confidence: 99%